A process for the application of modular architectural principles to system concept design. - Mackley, Timothy (Cranfield University, 2018)
A system architecture can be configured in ways that simplify both a system design and its development, by using established architectural principles such as independence and modularity. Despite systems design having been recognised as a discipline and a process as early as the mid-1900s, there are currently few methods available that address how these principles can be applied in practice. The literature search for this research has established a set of principles that can be used to develop a modular design, but has also shown that there are few formal methods available that will allow a system designer to apply such principles. This thesis examines what the key principles of modular architecture are and develops a process that enables the application of these principles to a system concept design. Key principles used are those of simplicity, independence, modularity and similarity. The concept of ‘context types’ is developed to allow the system designer to choose an architectural strategy that suits the system context. Another novel concept of ‘functional interaction types’ helps the system designer to identify critical interactions within the architecture that need to be addressed. Finally, the concept of functional interaction types is combined with existing measures of architectural ‘goodness’ to generate a method of evaluating the architecture that focusses on critical aspects. The process proposed is demonstrated by using a range of system examples and compared with the two of the most well-known methods currently available; Systematic Design and Axiomatic Design.
Keywords: Systems engineering; system design; system architecture; modularity; critical interaction modular design methodology; modular architecture